Local transformation of amorphous hydrogenated carbon coating induced by high contact pressure. (August 2018) - Fukumasu, N.K.; Bernardes, C.F.; Ramirez, M.A.; Trava-Airoldi, V.J.; Souza, R.M.; Machado, I.F.
Abstract: The development of coatings presenting adaptive characteristics based on mechanical loads would promote improved local characteristics. In this work, the surface modification of an a-C:H coating was analyzed based on the contact pressure using two tribological tests: lubricated reciprocating ball-on-plane and dry micro-scratch tests. Local transformation were evaluated based on Raman spectroscopy and indentation hardness. Results indicated regions presenting a red-shift of the G band and higher indentation hardness. High compressive stress field developed under the contacting region (numerical simulations) coupled to the red-shift of the G band and the increase on indentation hardness inside the tested regions are compatible with the nucleation of sp 3 carbon bond sites derived from sp 2 bonds, indicating a possible modification of the coating. Highlights: High contact pressure tribology measurements of Diamond like Carbon coatings. High correlation of higher indentation hardness on regions with increased sp 3 carbon bonds inside wear track. Damage calibrated model to reproduce realistic cohesive and adhesive coating failure by FEM model. Contact pressure and internal coating stresses were induced in the range of equilibrium formation of metastable diamond phase.